Environmental Sanitation Planning: Feasibility of the CLUES Framework in a Malawian Small Town - Mtika, Wema Meranda; Tilley, Elizabeth (Frontiers in Environmental Science, 2020)
Small towns are growing in size and number, but compared to the big cities that fuel economies, or rural areas that feed nations, small towns are generally less prioritized by governments and donors, both because they appear less immediately troublesome and because they defy easy classification. As such, growth has largely been unplanned for and remains unregulated, which means that responsible governments lack the commensurate tax base and political might to plan for and aquire the services they need to handle the changes that they face. For exactly these reasons, the Community-Led Urban Environmental Sanitation (CLUES) tool was developed to assist small towns with the planning and implementation of environmental sanitation infrastructure and services but we found no documented cases of it being used or evaluated. The goals of this work were to first, document the information obtained from the CLUES process as a case study for the condition of environmental sanitation in a small town in Malawi; and secondly, to evaluate the technical, political, and financial feasibility of the CLUES manual in a Malawian context. As facilitators, we guided the community and government through each of the 7 CLUES steps over the course of 2 years to understand the actual demands of the guidelines from the perspective of the user. Once the process was completed, we were able to critically reflect on our stated objectives and present those results here. The results of the process revealed that water quality was good (no measured E. coli at 45 water points) as was access to a sanitation facility, though water quantity was insufficient and fecal sludge management and solid waste collection required Council attention. However, because baseline data were outdated or non-existent, the data collection activities required to determine the status consumed unexpected amounts of time, and the results were, because of internal movement and politics, difficult to disseminate and leverage. Most importantly, stakeholder participation was limited and relied on participation and transportation payments, which have become a permanent feature of community development in Malawi. Following the CLUES process was expensive, time consuming and politically fraught; it is unlikely that any small town in Malawi would be able to follow the process as outlined. A simplified version, conducted by an in-house planning department should focus on identifying gaps, needs, and priorities, as a way of not only addressing environmental sanitation issues, but as a way to kick-start better data collection and management that can underscore long-term planning activities.